2013
DOI: 10.1016/j.cell.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Hippocampal Neurogenesis in Adult Humans

Abstract: Adult-born hippocampal neurons are important for cognitive plasticity in rodents. There is evidence for hippocampal neurogenesis in adult humans, although whether its extent is sufficient to have functional significance has been questioned. We have assessed the generation of hippocampal cells in humans by measuring the concentration of nuclear bomb test-derived 14C in genomic DNA and we present an integrated model of the cell turnover dynamics. We found that a large subpopulation of hippocampal neurons, consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
1,273
3
32

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,607 publications
(1,345 citation statements)
references
References 51 publications
37
1,273
3
32
Order By: Relevance
“…However, given the low number of new neurogenic cells produced in adulthood (Spalding et al, 2013), dendritic remodeling, synapse turnover, increased glial cell, and capillary density rather than neuronal replacement may account for ECT-induced volumetric changes (Bessa et al, 2009). Accordingly, Nordgren et al (2013) hypothesized that ECT causes transient downregulation of the key molecules needed to stabilize synaptic structures and to prevent calcium influx, and a simultaneous increase in neurotrophic factors, thus providing a short window of increased structural synaptic plasticity.…”
Section: Time Course Of Ect-induced Hippocampal Volume Changesmentioning
confidence: 99%
“…However, given the low number of new neurogenic cells produced in adulthood (Spalding et al, 2013), dendritic remodeling, synapse turnover, increased glial cell, and capillary density rather than neuronal replacement may account for ECT-induced volumetric changes (Bessa et al, 2009). Accordingly, Nordgren et al (2013) hypothesized that ECT causes transient downregulation of the key molecules needed to stabilize synaptic structures and to prevent calcium influx, and a simultaneous increase in neurotrophic factors, thus providing a short window of increased structural synaptic plasticity.…”
Section: Time Course Of Ect-induced Hippocampal Volume Changesmentioning
confidence: 99%
“…In the mouse neocortex, inheritance of the mother centriole maintains stemness; interfering with this process causes premature depletion of progenitors from the proliferative zone [79]. Why is this so?…”
Section: (Iii) Centrosome Asymmetry and Ciliogenesismentioning
confidence: 99%
“…However, in the most recent work of Spalding et al [22] neurogenesis throughout adulthood was found in the human hippocampus, adding to the plasticity of this important part of the brain (Fig. 7).…”
Section: Dating Human Dna With the 14 C Bomb Peakmentioning
confidence: 77%